2015
DOI: 10.15517/am.v26i1.16889
|View full text |Cite
|
Sign up to set email alerts
|

Comportamiento productivo del pasto ovillo (Dactylis glomerata L.) en respuesta al pastoreo.

Abstract: Productive behaviour of orchard grass (Dactylis glomerata L.) to sheep grazing management. The aim of this study was to determine the yield variation patterns in orchard grass (Dactylis glomerata L.) under grazing management. This study was performed in Montecillo, Texcoco state, Mexico from June 2005 to July 2006. Three grazing frequencies (21, 28 and 35 days) and two grazing intensities (5-7 and 9-11 cm residual sward high) were evaluated in a completely random block design with three replicates. The variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
1
2
0
3
Order By: Relevance
“…A seasonal yield distribution similar to that observed in the present study was reported by Villareal et al (2014) and Hernández et al (2015), in swards of orchard grass alone, and by Castro et al (2012), Flores et al (2015), Moreno et al (2015), and Rojas et al (2016a,b), in associated swards of orchard grass, perennial ryegrass, and white clover in the Valley of Mexico. The highest seasonal yields were registered during spring and summer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A seasonal yield distribution similar to that observed in the present study was reported by Villareal et al (2014) and Hernández et al (2015), in swards of orchard grass alone, and by Castro et al (2012), Flores et al (2015), Moreno et al (2015), and Rojas et al (2016a,b), in associated swards of orchard grass, perennial ryegrass, and white clover in the Valley of Mexico. The highest seasonal yields were registered during spring and summer.…”
Section: Discussionsupporting
confidence: 91%
“…During spring-summer, the perennial ryegrass monoculture and the 70:20:10 association of perennial ryegrass, orchard grass, and white clover obtained the highest forage yield. Villareal et al (2014) and Hernández et al (2015) reported, in monoculture of orchard grass, the highest yield in spring and summer and the lowest yield in fall and winter, regardless of the intensity and frequency of grazing. The association of white clover with orchard grass and perennial ryegrass yielded up to 52% more forage when the percentage of white clover in the sward was 40% and it could reach up to 65% more when grazing was done in spring-summer with a 28-day cut interval (Castro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Otro factor que afectó el comportamiento de los tallos fueron las competencias inter e intra-especifica por nutrientes, agua, luz y espacio (23) , ya que las plantas no rebrotan en una pradera como individuos aislados, sino como una población usualmente densa, donde la vegetación que los rodea ejerce una influencia muy fuerte sobre las características inherentes de cada especie, por medio de la competencia (24) . Otros autores, en el valle de México, reportan en ovillo asociado con las mismas especies (11) y en monocultivo (12) datos similares a lo encontrado en esta investigación.…”
Section: Análisis Estadísticounclassified
“…El mayor peso por tallo en las asociaciones se le puede atribuir a que existe un mayor aprovechamiento de recursos, ya que al estar asociado con la leguminosa y al poseer bacterias del género Rhizobium, fijan nitrógeno atmosférico al suelo y mediante simbiosis es aprovechado por las gramíneas, lo que ocasiona mayor rendimiento, peso por tallo y calidad, en comparación con la gramínea en monocultivo (29) . Estos resultados son similares a los encontrados por diferentes investigadores, quienes evaluaron el pasto ovillo asociado con ballico perenne y trébol blanco (30)(31)(32)(33) y en monocultivo (12,14,17) , obteniendo en primavera y verano el mayor forraje producido, lo cual está estrechamente correlacionado con el mayor peso por tallo. En asociaciones se han registrado mayores pesos por tallo de pasto ovillo en verano, relacionándolo con la mayor temperatura, similar a lo encontrado en esta investigación (11) .…”
Section: Análisis Estadísticounclassified
See 1 more Smart Citation